Quasi-simultaneous Optical Flux and Polarization Variability of the Binary Super Massive Black Hole Blazar OJ 287 from 2015 to 2023: Detection of an Anticorrelation in Flux and Polarization Variability - Alok C. Gupta; Pankaj Kushwaha; Mauri J. Valtonen; Sergey S. Savchenko; Svetlana G. Jorstad; Ryo Imazawa; Paul J. Wiita; Minfeng Gu; Alan P. Marscher; Zhongli Zhang; Rumen Bachev; G. A. Borman; et al. (The Astrophysical Journal Letters, 2023)
We study the optical flux and polarization variability of the binary black hole blazar OJ 287 using quasi-simultaneous observations from 2015 to 2023 carried out using telescopes in the USA, Japan, Russia, Crimea, and Bulgaria. This is one of the most extensive quasi-simultaneous optical flux and polarization variability studies of OJ 287. OJ 287 showed large amplitude, ∼3.0 mag flux variability, large changes of ∼37% in degree of polarization, and a large swing of ∼215° in the angle of the electric vector of polarization. During the period of observation, several flares in flux were detected. Those flares are correlated with a rapid increase in the degree of polarization and swings in electric vector of polarization angle. A peculiar behavior of anticorrelation between flux and polarization degree, accompanied by a nearly constant polarization angle, was detected from JD 2,458,156 to JD 2,458,292. We briefly discuss some explanations for the flux and polarization variations observed in OJ 287.